Implementation of SIAGUS in The Online Presence 0f Junior High School Teachers in The City of Surabaya - Vivia, Sandrina Della; Reviandani, Oktarizka (ARISTO, 2025)
This research aims to determine the implementation of the Surabaya teacher application information system in the online presence of junior high school teachers in the city of Surabaya. The SIAGUS application is the object of research because it is the only application to support teacher activities specifically in the city of Surabaya. This research methodology is descriptive qualitative with observation, interviews accompanied by documentation studies as a way to obtain data. The data was analyzed using the Rippley and Franklin theory quoted in (Yulianto Kadji, 2015) with the achievement of 3 sufficient indicators including the level of bureaucratic compliance, smooth routine and no problems and performance. The research results show that the SIAGUS application is here to make it easier for teachers to attend online, teachers feel helped and the level of teacher discipline after the application has clearly increased. even though there are obstacles such as the network on the application user's device and the resources of teachers who are classified as elderly. However, in this way the Surabaya City Education Office as teacher monitoring can resolve this problem